Women and Local Economic Resilience: Insights from Islamic Business Ethics in Maluku's Papalele Practices - Arizal Hamizar; Fitria Karnudu; Nur Mizwary Mustamin; Aep Saefullah (Sekolah Tinggi Agama islam Negeri Majene, 2026)
The informal sector remains a critical source of livelihood in Maluku despite the province's strong economic growth. This study aims to analyze the role of Papalele women in strengthening local economic resilience, explore consumer behavior toward Papalele traders, and examine the implementation of the Islamic business ethics principle of ṣidq (truthfulness) in traditional market practices. A qualitative descriptive approach was employed in Ambon, Maluku. Data were collected through in-depth interviews with Papalele women traders and consumers, complemented by participant observation and documentation. The data were analyzed using the Miles and Huberman interactive model. The findings reveal that Papalele women serve as key economic actors who sustain household livelihoods and function as shock absorbers in the local economy amid economic and environmental uncertainties. Their contributions extend beyond income generation to maintaining the circulation of local goods and supporting community welfare. Consumer engagement with Papalele traders is shaped by three interrelated factors: trust, time efficiency, and social solidarity. Furthermore, the principle of sidq is practiced through honesty, transparency, and fairness in transactions, enabling traders to build consumer trust, reduce transaction uncertainty, and strengthen long-term market relationships. This study implies that local economic resilience is not solely determined by macroeconomic growth but is also sustained by women-led informal economic activities grounded in ethical values. The findings highlight the importance of integrating Islamic business ethics into community-based economic development strategies while recognizing the significant contribution of women traders to resilient and inclusive local economies